The Effect of Saving and Investment to Economic Growth in Maluku Province - Teddy Christianto Leasiwal; Bin Raudha A. Hanoeboen; Celine Tamaela; Abdul Aziz Laitupa; Lussi Lopies (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aimed to analyze the effect of saving and investment to economic growth in Maluku Province. The data used in this research is secondary data obtained from the Central Statistics Agency and Bank Indonesia for the 2015-2019 period. Data analysis using data-panel regression analysis. The results of this research found that saving had a positive and significant effect to economic growth and investment had a positive and insignificant effect to economic growth in Maluku Province. Savings are positively and significantly related to economic growth because the average income of the people in Maluku Province is used for consumption and in savings. Investment is positively and not significantly related to economic growth because when there is investment there is employment, but the absorption of labor is not optimal so that investment is not significant in the reality.